Kajian Kesesuaian Lahan Untuk Tanaman Jagung Menggunakan Sistem Informasi Geogarafi Di Sebagian Wilayah Desa Sea Dan Warembungan Kecamatan Pineleng. - Selfina Emilince Hegemur; Dr. Ir. Joudie N. Luntungan MSi; Dr. Ir. Diane D. Pioh, MSi (COCOS, 2019)
SUMMARY The purpose of this study was to determine the suitability of land for maize in parts of the Sea and Warembungan villages of Pineleng Distriet. The research method used was a survey method soil. Sampling is done based on land units. Land units are arranged based on land use, Slope and soil type. The results showed that the limiting factor is rainfall needs to be improved irrigation and soil conservation capacity, namely the making of drainage so that the actual land suitability after N will trun into a potential land suitability for class S2 and S3. Keywords : Maize Crops and Geographic information system.